2017
DOI: 10.1093/pcp/pcx169
|View full text |Cite
|
Sign up to set email alerts
|

Suppressing Type 2C Protein Phosphatases Alters Fruit Ripening and the Stress Response in Tomato

Abstract: Although ABA signaling has been widely studied in Arabidopsis, the roles of core ABA signaling components in fruit remain poorly understood. Herein, we characterize SlPP2C1, a group A type 2C protein phosphatase that negatively regulates ABA signaling and fruit ripening in tomato. The SlPP2C1 protein was localized in the cytoplasm close to AtAHG3/AtPP2CA. The SlPP2C1 gene was expressed in all tomato tissues throughout development, particularly in flowers and fruits, and it was up-regulated by dehydration and A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(29 citation statements)
references
References 43 publications
2
26
0
1
Order By: Relevance
“…Here, the expression of NCED1 , which is involved in ABA biosynthesis, was highly up-regulated during ripening, suggesting that ABA biosynthesis and signal transduction was induced. In tomato, SlPP2C1-RNAi led to increased endogenous ABA accumulation and significantly accelerated fruit ripening and altered the expression of fruit ripening genes involved in ethylene release and cell wall catabolism [34]. In our study, PP2C11 , PP2C27 , PP2C33 , SnRK2 were down-regulated and ABF2 was up-regulated during ripening, indicating that the PYR1-PP2C-SnRK2 pathway was activated, consistent with previous studies [21].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Here, the expression of NCED1 , which is involved in ABA biosynthesis, was highly up-regulated during ripening, suggesting that ABA biosynthesis and signal transduction was induced. In tomato, SlPP2C1-RNAi led to increased endogenous ABA accumulation and significantly accelerated fruit ripening and altered the expression of fruit ripening genes involved in ethylene release and cell wall catabolism [34]. In our study, PP2C11 , PP2C27 , PP2C33 , SnRK2 were down-regulated and ABF2 was up-regulated during ripening, indicating that the PYR1-PP2C-SnRK2 pathway was activated, consistent with previous studies [21].…”
Section: Discussionsupporting
confidence: 91%
“…The plant hormone ethylene plays a major role in the ripening and quality formation of climacteric fruit [34]. In this work, we observed that the expression of an ACS2 and an ACO1 , families of which are central ethylene biosynthesis, were significantly up-regulated during ripening, while the expression of ETR , an ethylene receptor, decreased significantly.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…In contrast, silencing of three CYP707A2 isoforms, encoding ABA 8 0 -hydroxylases acting in ABA catabolism, or of ABA uridine diphosphate glucosyltransferase (SlUGT75C1), which produces esterified ABA-glucose, generated over-ripe fruits with increased ABA levels (Ji et al, 2014;Sun et al, 2017). A similar phenotype was observed in RNAi lines for SlPP2C1, a group A type 2C protein phosphatase involved in ABA signalling (Zhang et al, 2018). These observations suggest that ABA influences fruit ripening in different ways, depending on the mode (external or endogenous) and timing of the application.…”
Section: Introductionmentioning
confidence: 85%
“…In Arabidopsis, PP2Cs interacts with SnRK2s and inhibits the kinase activity as it dephosphorylates key serine residues in the kinase activation loop, and physically blocking the kinase catalytic site (Belin et al, 2006;Vlad et al, 2009;Soon et al, 2012). In angiosperms, group A PP2C contains multi-genes with redundant function (Leung et al, 1994;Meyer et al, 1994;Leung et al, 1997;Rodriguez et al, 1998;Saez et al, 2004;Schweighofer et al, 2004;Xue et al, 2008;Zhang et al, 2018;Fujioka et al, 2019). High-order of loss-of-function Arabidopsis mutant of PP2C displays an increase of ABA sensitivity, and partially constitutive ABA response (Saez et al, 2006;Rubio et al, 2009).…”
Section: The Pp2c-snrk2 Signaling Module Throughout Plant Evolutionmentioning
confidence: 99%